Anticeramide Improves Sjögren's Syndrome by Blocking BMP6-Induced Th1. (January 2023) - Li, J.; Wu, L.; Chen, Y.; Yan, Z.; Fu, J.; Luo, Z.; Du, J.; Guo, L.; Xu, J.; Liu, Y.
T-cell dysfunction has been shown to play an important role in the pathogenesis of Sjögren's syndrome (SS). In recent studies, the increased expression of BMP6 has been reported to be related to SS. However, the roles that BMP6 plays in immune homeostasis in the development of SS as well as the downstream signals activated by BMP6 remain unclear. In this study, we investigated the effects and molecular mechanisms of BMP6 on naive CD4 + T cells, showing that BMP6 could upregulate interferon (IFN)–γ secretion from CD4 + T cells through a ceramide/nuclear factor–κB pathway, with no effect on T-cell activation or proliferation. Moreover, an in vivo study showed that anticeramide treatment (myriocin) for an SS animal model (NOD/LtJ mice) could significantly decrease the IFN-γ expression and Th1 frequency in the salivary glands and suppress the inflammation infiltration in salivary glands and maintain the salivary flow rates, both of which reflect SS-like symptoms. This study identifies a promising target that could effectively attenuate the abnormal state of CD4 + T cells and reverse the progression of SS.